Indexação de Documentos Clínicos - João de Sá Balão Calisto Correia (2016)
Nowadays access to structured and well organized information is increasingly important in the planning, development and performance of a company. In a clinical environment, the access to this type of information influences the services provided by the medical entities, since the information is too dispersed by various sources. Thus it becomes clear that innovating access to information on these services is essential to improve efficiency and quality. In the perspective of improving these services, there is the indexation of clinical documents solution, which enables the extraction of several documents in various formats of a Glintt database, and index, and provides its information in a search area. The formats in question can be PDF, Word, XML, JSON and more. Regarding the content of the information we have for example: laboratory analytical results, clinical reports, diagnoses coded in ICD-9, clinical notes from doctors, requisitions, drug prescriptions and demographic information of patients. In order to reduce the requests to the database in question and, to a greater standardization of information follows the EHR standard while, for indexing purposes, we use Solr. This project is intended to health professionals and therefore provides a centralized, searchable way to get all the clinical data of a patients and the corresponding documentary information. That said, the solution aims to have a strong impact on the day-to-day health professionals as well as their patients, making access easier and faster clinical information.